Penerapan Metode Pencatatan dan Penilaian Persediaan Barang Dagangan - Syahrani, Umita; Evada Dewata; Yuliana Sari (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2024)
This activity aims to find out how to apply the method of recording and assessing merchandise inventory at PT MMA and to compare the method of recording and assessing inventory according to PT MMA with the method of recording and assessing based on SAK ETAP, namely the perpetual method and the FIFO method. This activity was carried out using the interview method and analyzing data together with parties from PT MMA. The results of the analysis related to recording merchandise inventory show that PT MMA includes 11% VAT in the inventory acquisition price, this is not in accordance with SAK ETAP. Meanwhile, the results of the analysis related to inventory assessment show that there is a difference in the ending inventory value of Swiss fold and Trypan blue products according to the Company using the FIFO method. This happens because PT MMA recognizes that the initial cost of inventory will follow the most recent cost of goods purchased, while the FIFO method recognizes that the first goods purchased are the first goods sold so that applying the perpetual and FIFO methods will help PT MMA to be able to find out inventory value periodically appropriately based on SAK ETAP.